Pembuatan Sistem Zona Integritas Di Akademi Kepolisian Menggunakan Metode Rapid Application Development (RAD) - Purwono; Eka Ardhianto (Universitas Sari Mutiara Indonesia Medan, 2023)
The Integrity Zone is one of the programs implemented in various government institutions, including the PoliceAcademy, to improve public services and strengthen good governance. In this context, the development ofinformation technology-based systems is crucial to support the efficiency and effectiveness of programimplementation. This study aims to develop an Integrity Zone System at the Police Academy using the RapidApplication Development (RAD) Method. The RAD method was chosen because of its ability to speed up thesystem development process through the use of prototypes that can be changed and adapted to user needs. Theresult of this research is the Integrity Zone System at the Police Academy which has been developed using theRAD Method. This system is able to facilitate the implementation of the Integrity Zone more efficiently andeffectively. Through the features provided, users can manage and monitor activities related to the IntegrityZone, collect and analyze data, and generate the required reports. This research is expected to contribute tothe development of information technology in government institutions, especially in the implementation of theIntegrity Zone program. The RAD method used in this study can also be a reference for other system developersin dealing with projects with tight deadlines and fast changing needs..